Efektivitas Pembelajaran Berbasis Crossword Puzzle untuk Meningkatkan Kemampuan Berpikir Kritis (Critical Thinking) Pada Siswa: Literatur Review - Gulo, Christiani Des Marindra; Muhid, Abdul (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2024)
The crossword puzzle is an efficient approach to increasing student participation in the learning process. This method allows for discussions in both large and small groups, enabling students to actively participate in learning activities. By implementing this active learning method, students can more easily understand the material or lessons presented by the educator. Critical thinking is an essential skill that helps in making logical decisions based on concrete evidence. This process involves formulating problems, searching for arguments, performing deduction and induction, evaluating information, and ultimately making decisions. Currently, many teaching models are introduced by each teacher in schools. The development of education in Indonesia still does not nurture student creativity because schools only measure students' cognitive levels, resulting in low creativity levels among Indonesian students. Using crossword puzzles as a learning medium is proposed as a solution to enhance students' creativity, particularly junior high school students. Therefore, this research aims to analyze the benefits of crossword puzzles as a tool to increase student creativity. This analysis is conducted by gathering various scientific literature sources related to the research variables. The results of the literature review indicate that using crossword puzzles as a learning medium can enhance the creativity of junior high school students.